2014
DOI: 10.1371/journal.pone.0103508
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux in Relation to Adenocarcinomas of the Esophagus: A Pooled Analysis from the Barrett’s and Esophageal Adenocarcinoma Consortium (BEACON)

Abstract: BackgroundPrevious studies have evidenced an association between gastroesophageal reflux and esophageal adenocarcinoma (EA). It is unknown to what extent these associations vary by population, age, sex, body mass index, and cigarette smoking, or whether duration and frequency of symptoms interact in predicting risk. The Barrett’s and Esophageal Adenocarcinoma Consortium (BEACON) allowed an in-depth assessment of these issues.MethodsDetailed information on heartburn and regurgitation symptoms and covariates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 25 publications
3
115
0
4
Order By: Relevance
“…Short-term data suggest that POEM is as effective as LHM in treating dysphagia with similar rates of postoperative reflux although randomized controlled trials have yet to be performed [17][18][19]. In cohort studies, postoperative reflux is reported in 0-53 % of patients following POEM [6][7][8][20][21][22]. Some of this variability may relate to differences in subjective and objective measurements of acid reflux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term data suggest that POEM is as effective as LHM in treating dysphagia with similar rates of postoperative reflux although randomized controlled trials have yet to be performed [17][18][19]. In cohort studies, postoperative reflux is reported in 0-53 % of patients following POEM [6][7][8][20][21][22]. Some of this variability may relate to differences in subjective and objective measurements of acid reflux.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Heller myotomy, no anti-reflux procedure is included and the rate of postoperative reflux has varied widely from 0 to 53 % in published studies [2][3][4]. This variation has created debate as to whether all patients should be treated with acid suppression postoperatively to avoid the complications of uncontrolled reflux such as erosive esophagitis, peptic stricture, and Barrett's esophagus [5][6][7].An alternative to lifelong treatment with proton pump inhibitors (PPI) is tailored PPI use based on the presence of …”
mentioning
confidence: 99%
“…Moreover, obesity, especially central type, and gastroesophageal reflux disease are risk factors toward developing esophageal adenocarcinoma [5,6]. On the other hand, healthy dietary habits could be a shield against some types of esophageal cancer [7], while nutritional support could be beneficial for the management of these patients after cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…49-5.25) in the presence of reflux symptoms, of 5.85 (95% CI 3.18-10.75) in case of a hiatus hernia and of 8.11 (95% CI 4.75-13.87) in case of both factors being present [10]. There is a clear need for non-invasive tools for identifying patients at risk who do not present with typical symptoms [5,11]. Blood-based markers would be most feasible regarding clinical applicability.…”
Section: Primary Preventionmentioning
confidence: 99%